PEMBERDAYAAN PETANI MELALUI PENDAYAGUNAAN LAHAN YANG EFEKTIF DAN SISTEM AGRIBISNIS MODERN - -, Priyono - (Joglo, 2003)
ABSTRACT Effect the population density in Indonesia to their land reduce until 0,4 ha per person. Because their land is used to develop many factories, offeces, shopping centres, houses, roads, etc. The farmers rising problem about decreasing plant production such as rice, corn, soya bean, peanut, etc. Because they are needed to solve the problem, to give their motivation and the real thing, to improve their economics and their life by using effective land use and agrobussiness modern system. The read forms are : 1) increase self respect and prestige of farmers by land use reform/agrarian reform, 2) by using narrow land in order to increase the effective and sustainable use, 3) to be expects in post harvest and processing in agriculture product, also to be good capable in marketing, 4) to give learning and taining, to conctruct in agrobussiness modern too, 5) regulate the rule trading agriculture commodities which are more benefits, 6) to provide hardware and software agriculture commodities, 7) to control stability price and care more benefits for farmers. Key word : Rise the efforts farmers, land use, and agrobussiness modern system